The World Bank Land and Poverty Conference 2019: Catalyzing Annovation - Nau, S. Zaung; Marinova, Dora (2019)
The purpose of this paper is to identify the urban and rural regional profiles of socioeconomic indices at the township level in Myanmar. It aims to identify and rank the urban and rural areas according to relative socioeconomic advantage and disadvantage based on the level of education, literacy, employment, type of occupation, housing and living standard variables which are contributing to inequality at the geographical township level. Moreover, it also aimed to examine how land use characteristics such as agricultural land, mining areas, forestry, transport infrastructures such as inland transport routes and trade routes and geographical features are relating with these socioeconomic profiles in different regions.